Writing for My Future: Transition-Focused Self-Advocacy of Secondary Students With Emotional/Behavioral Disorders. (April 2019) - Cuenca-Carlino, Yojanna; Mustian, April L.; Allen, Ruth D.; Whitley, Samuel F.
Nine high school students with emotional and behavioral disorders received instruction on how to write argumentative essays to self-advocate for their transition-focused needs. A special education teacher and paraprofessional received training on the self-regulated strategy development (SRSD) model of writing instruction. They provided instruction to students 3 days a week, 40 min each session, for 12 to 14 days of strategy instruction. The teacher and the paraprofessional provided instruction with high fidelity. Using a single-subject multiple-probe-across-groups design, findings indicated a functional relation between SRSD instruction and all students' writing skills. Students' essays increased for organizational quality and self-advocacy in writing. Furthermore, students' writing self-efficacy increased as a result of instruction. Teacher and student interviews revealed an overall satisfaction with SRSD procedures and results.